2022
DOI: 10.3390/coatings12111679
|View full text |Cite
|
Sign up to set email alerts
|

Silver and Silver Nanoparticles for the Potential Treatment of COVID-19: A Review

Abstract: COVID-19 is an epizootic and life-threatening outbreak affecting millions of people globally. Coronavirus variants have emerged in different locations since their origin. Silver and its compounds, including silver nanoparticles (AgNPs), have been used in the medical field for a long period, especially in surgical treatments. The anti-microbial and anti-viral properties of silver are well documented. These properties depend on the size of the particles, concentration, precursor, method of preparation, and the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 141 publications
0
4
0
Order By: Relevance
“…48 Algal powder (1 mg) was dissolved in 2 mL of distilled water, boiled at 60 °C for 20 min and filtered using filter paper. Then, 2 mL of algal filtrate was mixed with 1 mL of 1 mM AgNO 3 at pH 5.5 and incubated for 24 h. The authors also controlled three optimization parameters including temperature (30, 40, 50, 60 °C), pH (3.5, 5.5, 7.5 and 9.5), and (1,12,24,48, and 72 h). These scholars found that optimum conditions for synthesizing AgNPs were a temperature of 60 °C, pH 5.5, and time period of 72 h. 5).…”
Section: Gc-ms Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…48 Algal powder (1 mg) was dissolved in 2 mL of distilled water, boiled at 60 °C for 20 min and filtered using filter paper. Then, 2 mL of algal filtrate was mixed with 1 mL of 1 mM AgNO 3 at pH 5.5 and incubated for 24 h. The authors also controlled three optimization parameters including temperature (30, 40, 50, 60 °C), pH (3.5, 5.5, 7.5 and 9.5), and (1,12,24,48, and 72 h). These scholars found that optimum conditions for synthesizing AgNPs were a temperature of 60 °C, pH 5.5, and time period of 72 h. 5).…”
Section: Gc-ms Analysismentioning
confidence: 99%
“…Physical and chemical methods are the most commonly used routes for fabricating NPs however their limitations such as high production costs, low scalability, energy consumption, and high-yield toxic substances limit their use. 1 , 2 To overcome these tackles, researchers have begun to use green synthesis to produce metals in nanoform. Green synthesis of nanoparticles (NPs) is one of the most reliable and sustainable techniques for NP production.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding antiviral activity, AgNPs have unique virus-targeting characteristics and can easily bind to viral surface glycoproteins [ 13 ]. Then, AgNPs can enter the virus cells to exhibit virucidal activity by attacking the viral genome [ 14 ]. Given the antiviral and virucidal potential of AgNPs, some studies have investigated their inhibition application in PPE and CPE [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was concluded that AgNPs are strongly bound to the SARS-CoV-2 virus eliminating its binding on the host cell. This may lead to virus death [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%